159k views
1 vote
-(-6r + 8) − 6 = 6(r – 5)

User Tola
by
6.0k points

1 Answer

1 vote

Hi, there.

______

First off, distribute - through the parenthesis:


\boldsymbol{-(-6r+8)=6r-8}

Replace
\boldsymbol{-(-6r+8)} with
\boldsymbol{6r-8}:


\boldsymbol{6r-8-6=6(r-5)}

Combine like terms:


\boldsymbol{6r-14=6(r-5)}

Distribute 6 through the parenthesis:


\boldsymbol{6(r-5)=6r-30}

Make the replacement:


\boldsymbol{6r-14=6r-30}

Subtract 6r from both sides:


\boldsymbol{6r-6r-14=6r-6r-30}


\boldsymbol{-14=30}

Uh-oh!

Actually,


\boldsymbol{-14\\eq-30}

Answer:


\boldsymbol{No \ solution}

Hope the answer - and explanation - made sense,

happy studying!!

User Asdjfiasd
by
6.2k points